2010
DOI: 10.1080/10934529.2010.520605
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal trends of heavy metal concentrations in fish of the River Morava (Danube basin)

Abstract: The aim of this study was to assess mercury (Hg), cadmium (Cd) and lead (Pb) contamination in muscle tissue of fishes over the longitudinal profile of the River Morava (Czech Republic, Danube basin) and to detect any temporal trends over the past 18 years. Fish samples were collected in 1992, 1998, 2000, 2003 and 2009 at 6 study sites situated just downstream of important pollution sources. Chub (Leuciscus cephalus L.) were selected as indicator species at 5 sites, and brown trout (Salmo trutta m. fario L.) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
2
10
1
Order By: Relevance
“…2). These values are in accordance with the studies of Valová et al (2010;River Morava) and Spurný et al (2009;River Jihlava), in which total Hg concentrations in chub muscle tissue varied between 0.015 and 0.369 mg/kg and 0.040 and 0.133 mg/kg, respectively. Kružíková et al (2008) also found low Hg concentrations in chub muscle from the rivers Morava and Dyje in their study of 10 Czech rivers.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…2). These values are in accordance with the studies of Valová et al (2010;River Morava) and Spurný et al (2009;River Jihlava), in which total Hg concentrations in chub muscle tissue varied between 0.015 and 0.369 mg/kg and 0.040 and 0.133 mg/kg, respectively. Kružíková et al (2008) also found low Hg concentrations in chub muscle from the rivers Morava and Dyje in their study of 10 Czech rivers.…”
Section: Resultssupporting
confidence: 91%
“…Dušek et al 2005;Houserová et al 2006;Havelková et al 2008;Kružíková et al 2008;Radnák et al 2009;Spurný et al 2009;Valová et al 2010). The chub Squalius cephalus L., a common freshwater cyprinid species, is considered the most suitable model fish species for such studies in rivers of the Czech Republic as they inhabit both clean and polluted waters (Baruš and Oliva 1995), occur along most of the longitudinal profile of Central European rivers, are omnivorous and have a body large enough for taking analytical samples of muscle tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Many countries in the world have experienced menace of metal pollution in water, and a large number of people have been affected. Causes of this pollution have been well documented by (Voutsa et al 1995;Newchurch and Kahwa 1984;Tariq et al 1993;Chukwujindu et al 2012;Samanidou and Papadoyannis 1992;Sharma et al 1992;Valová et al 2010). However, the primary sources of metal toxicity in surface water have been thought to be the natural occurrence and subsequent degradation of the environment (Jessica et al 2011).…”
Section: Metal Toxicitymentioning
confidence: 99%
“…Prepare and propose projects on priority hotspots in this aquatic system. Strengthen the capacities of environmental organisations and improve the international cooperation on sustainable management of the hydrosystem on trophic and sanitary basis as expressed by the findings of [20,21].…”
Section: Discussionmentioning
confidence: 99%